Espying heaven : the stained glass of Charles Eamer Kempe and his artists - Barlow, Adrian (The Lutterworth Press, 2019)
A lavishly-illustrated exploration of the work of the Victorian church artist Charles Eamer Kempe and the team of artists he led and inspired.